Mechanical, electrical, and thermal analysis of sisal fibril/kenaf fiber hybrid polyester composites. Issue 2 (29th December 2017) - Nimanpure, Subhash; Hashmi, S.A.R.; Kumar, Rajnish; Bhargaw, H.N.; Kumar, Rajeev; Nair, Prasanth; Naik, Ajay
Abstract : A novel hybrid composition of sisal fibrils and kenaf fibers has been introduced first time as reinforcement in composite preparation for the environmental friendly high strength electrical insulation applications. Hybrid reinforcement was increased from 10 to 40 wt% in unsaturated polyester resin. The sisal fibril used in this study was extracted from sisal fiber. Alkali treatment was employed and FTIR analysis was done to study its effect on sisal fibrils and kenaf fibers. A positive hybridization effect was observed for the composites. Hybrid composite showed 24 and 18% increase in tensile strength, 30 and 36.4% increase in flexural strength, and 196.3 and 196% increase in impact strength as compared to the composites having same loading of 40 wt% with sisal fibrils and kenaf fibers, respectively. Scanning electron microscopy of the fractured mechanical testing samples was carried out to understand the nature of fibril/fiber/matrix interface. Electrical characterization showed high electrical insulation capability of the hybrid composites. Thermal stability of hybrid composites was also found higher than sisal fibrils and kenaf fibers reinforced composites. A comparative study of properties of sisal fibril/kenaf fiber reinforced hybrid polyester composites with various single and hybrid fiber composites is done. It has been concluded that the developed novel hybrid composite has the potential to replace various existing natural and synthetic fiber composites. POLYM. COMPOS., 40:664–676, 2019. © 2017 Society of Plastics Engineers